TRANSFORMASI PROFESI AKUNTANSI DI ERA KECERDASAN BUATAN: PELUANG, TANTANGAN, DAN KETERAMPILAN BARU YANG DIBUTUHKAN - Amyati, Amyati; Sari, Diah Permata; Sumarsih, Rani Sri (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
The advancement of technology, particularly Artificial Intelligence (AI), big data, and automation, has significantly transformed the accounting profession. This article examines the impact and challenges faced by the accounting profession in the digital era, as well as the new skills required for accountants to remain relevant. Through a literature review approach, this study finds that technology has replaced many routine tasks traditionally performed by accountants, such as transaction recording and financial reporting, thereby enabling higher efficiency. However, these advancements also raise concerns about the diminishing role of accountants in their conventional functions. The primary findings indicate that the main challenges in technology adaptation within the accounting profession include resistance to change, limited technical skills, and unequal access to infrastructure across organizations. Additionally, this article highlights the importance of new skills, such as data analysis, basic programming knowledge, and creative problem-solving abilities for addressing complex issues. Effective communication skills are also increasingly crucial for bridging technical data with business strategy needs. This article concludes that accountants need to develop technology-based competencies and strategic capabilities to support their roles in corporate decision-making. Therefore, organizational support in the form of training and technological education is essential to ensure that the accounting profession continues to grow and remain relevant in the era of artificial intelligence